Analysis of Grade X MA Students’ Mathematical Difficulties in Solving SPLTV Contextual Problems through Group Discussion - Fahmi Abdul Halim; Vandana Rindang Arandany; Devi Rahayu Agustin; Putri Lamanda Frisca; Adinda Laili Yuli Andira (CV. Edujavare Publishing, 2026)
Students’ mathematical difficulties in solving contaxtual problems on the topic of Systems of Linear Equations with Three Variables (SPLTV) remain an issue theat requires further study, particularly as viewed through the lens of the group discussion process undertaken by students. This study aims to analyze the types and characteristics of mathematical difficulties experienced by 10th-grade students in solving contextual problems involving SPLTV, as observed through homogeneous and hererogeneous group discussions. The study employed a descriptive qualitative approach with 21 student from MA Hasyim Asy’ari Lbruk Kidul Lumajang as subjects, divide into six discussion groups: three homogeneous groups (low, moderate, and high difficulties categories) and three heterogeneous group. Data were collected through the Contextual Probblem Solving (TPK), in depth interviews, observations, and documentation, and were then analyzed through data reduction, data presentation, and drawing conclusions. The results showed that students experienced three types of mathematical difficulties: conceptual, procedural, and representational. The group with active discussion experienced only mild representational difficulties, where as the group categorized as having high difficulty scores-whose discussions were less active-experienced all three types of difficulties are more influenced by the quality of their enggagement in group discussions than by their initial ability categories; thus,active group discussions play a crucial role in reducing students’ mathematical difficulties with the SPLTV matrial.